Religion and Spirituality in Korean America - Chung, Ruth H.; Yoo, David (Book collections on Project MUSE., 2008)
Religion and Spirituality in Korean America examines the ambivalent identities of predominantly Protestant Korean Americans in Judeo-Christian American culture. Focusing largely on the migration of Koreans to the United States since 1965, this interdisciplinary collection investigates campus faith groups and adoptees and probes how factors such as race, the concept of diaspora, and the improvised creation of sacred spaces shape Korean American religious identity and experience.